Socio-personal contour, information flow and productivity of brackishwater aquaculture systems - An Appraisal - M, Kumaran; M, Sundaram; Mathew, Shijo Mathew; PR, Anand (Journal of Extension Education, 2019)
Brackishwater aquaculture, the farming of shrimps and fishes in coastal areas is practiced both in traditional and scientific methods. A study was conducted to assess the connectedness between the profile characteristics, their information sourcing and productivity levels. The study indicated that systems and states differ significantly (p<0.01) both in terms of profile status and productivity levels. Private extension services were dominant in scientific farming while traditional systems depend on state fisheries departments for inputs and technical advisory. Therefore, taking into account the relative strengths the state departments may partner with research institutions and input companies respectively for technology support and reaching the farmers located in remote locations. Mobile phone applications may be developed and launched for connecting the technology, inputs, services and market with the farming community.